Is the South-Mediterranean Canopy-Forming Ericaria giacconei (= Cystoseira hyblaea) a Loser From Ocean Warming? - Falace, Annalisa; Marletta, Giuliana; Savonitto, Gilda; Candotto Carniel, Fabio; Srijemsi, Marina; Bevilacqua, Stanislao; Tretiach, Mauro; Alongi, Giuseppina (Frontiers in Marine Science, 2021)
Canopy-forming brown algae support highly productive ecosystems whose decline has been attributed to the interplay of several anthropogenic disturbances. Climate change could have disruptive effects on the biology of these species, but the role of temperature in the development of early life stages is poorly understood. The aim of this study was to evaluate the response of Ericaria giacconei, a winter-reproducing Southern-Mediterranean endemic species, to thermal stress by testing five temperatures (12, 15, 18, 24, 28 °C) on adults and early stages. Chlorophyll a fluorescence of adult plants was measured at 0, 24, 72, and 120 hours on nine fronds in each of the three aquaria per treatment. To assess egg release, zygote settlement, and embryo growth rate, approximately 1200 receptacles were cultured on six Petri dishes per temperature treatment, and 10 random subsections of 2 x 2 mm were examined in three Petri dishes at 0, 20, 44, and 92 hours after fertilization. Adult plants showed a plastic physiological response, and thermal stress had no significant effect on PS II efficiency. Embryos fully developed only at 12 and 15 °C. Mortality increased at 18 and 24 °C, and no zygotes survived at 28 °C. In a scenario of further increasing temperatures, the effects of warming could affect the recruitment of E. giacconei and increase its vulnerability to further stresses. These effects on the survival of early stages, which are the bottleneck for the long-term survival of the species, should be taken into account in conservation and restoration measures to maintain canopy-forming macroalgal populations and associated biodiversity and ecosystem services.